What Do We Know About Staphylococcus aureus and Oxidative Stress? Resistance, Virulence, New Targets, and Therapeutic Alternatives - Mírian Letícia Carmo Bastos; Gleison Gonçalves Ferreira; Isis de Oliveira Kosmiscky; Ieda Maria Louzada Guedes; José Augusto Pereira Carneiro Muniz; Liliane Almeida Carneiro; Ísis Lins de Carvalho Peralta; Marcia Nazaré Miranda Bahia; Cintya de Oliveira Souza; Maria Fâni Dolabela (Toxics)
Staphylococcus aureus is associated with human infections, being a resistant bacterium involved in serious infections, and its virulence and resistance are linked to oxidative stress. In this study, we review the role of oxidative stress in the pathogenesis of this bacterium and its influence on immune system evasion, antibiotic resistance, and pharmacological targeting. S. aureus infection generates an intense inflammatory response in the host, evidenced by the activation of pro-inflammatory pathways, the exacerbated production of reactive oxygen species (ROS), and cellular oxidative stress. However, the bacterium develops protective mechanisms against damage, including the production of endogenous antioxidants, the formation of biofilms, and the regulation of redox metabolism, favoring pathogenicity and drug resistance. Resistance seems to be related to alterations in redox metabolism, which influences the sensitization of the immune system. Modulation of the redox response has emerged as a promising approach for developing new antibiotics and formulating more effective combination therapies to combat resistant infections. Natural compounds, including flavonoids, terpenes, and quinones, have demonstrated antibacterial properties by inducing oxidative stress in S. aureus. In summary, the involvement of oxidative stress is complex, with an increase in ROS in the infection and a reduction in immune system evasion and resistance, which could be an interesting therapeutic target.